Comparison of additive and multiplicative feedforward control. (March 2022) - Luyben, William L.
Abstract: Feedforward control has been widely used for many years to improve the closedloop dynamic response of chemical processes to load disturbances compared to simply using feedback control. If the disturbance can be measured, a feedforward control element can immediately begin to move the appropriate manipulated variable to lessen the deviation in the controlled variable. Two types of feedforward structures have been used. Most academic studies consider a structure in which the output signals from the feedback controller and the feedforward controller are added to produce the manipulated variable in the process. Most applied studies consider a structure in which the ratio of the manipulate variable to the load disturbance is adjusted by the output signal of a feedback controller (multiplicative feedforward). The feedback controller adjusts the gain of the feedforward controller. The purpose of this paper is to present a quantitative comparison of these two approaches for two important examples: a distillation column and a chemical reactor. Highlights: Additive and multiplicative feedforward/feedback control structures are studied. Common practice uses the more simple multiplicative ratio structure. The additive structure is demonstrated to give more effective load rejection in two important examples (distillation and CSTR).